Examining the Internet Quota Subsidy Policy in Indonesia - Sajida Sajida; Ranjani Ranjani (Iapa Proceedings Conference, 2020)
The pandemic in Indonesia requires a moving from offline learning to online learning to reduce the spread of COVID-19. However, that practice facing some problem like the increment households spending for internet access, and inequality access technology. As a form of accountability and responsibility for these problems, the Indonesian government by the Ministry of Education and Culture made a policy of subsidizing internet quota for all teachers, students, and lecturers for four months. This subsidy was made to support distance learning during the pandemic. This article aims to examine the implementation of the internet quota subsidy policy. The literature review method is carried out by looking at previous research related to aid/subsidies policies during the crisis, policy implementation, and internet quota subsidy in Indonesia. The sources were collected from articles, reports, and mass media. The results show that looking at the output and the initiation, this policy has been running quite well as part of the government's agility response. However, this policy was not effective enough to support distance learning during the pandemic as a whole in Indonesia. Several findings indicate there is inequality of internet access in some outlying areas where the benefits of this policy cannot be felt.